Thermal dielectric and Raman studies on the KNO3 compound high-temperature region (2016)
Calorimetric measurements for a heating-cooling cycle determine the transition temperature and enthalpy of the phases present in the KNO3compound. The effects correlated within the ionic conduction of the KNO3 compound were studied by impedance spectroscopy measurements in a frequency range from 0.1 to 10 MHz for a cooling cycle. The imaginary part of the impedance with a frequency between 200 and 100°C showed a displacement of the Debye-like peak in the lower frequency direction. This displacement indicates an increase in the relaxation times of ionic conductivity by jump. In the dielectric formalism module, the imaginary part showed an asymmetric peak as a correlation consequence in the cationic diffusion. Also the registers demonstrated that the process is thermally activated, with activation energy that is very close to the one obtained for dc conduction. From these results, it can be inferred that both, diffusion and conductivity mechanisms have the same origin. The Raman spectroscopy measurements, based on temperature (when cooling), allowed for correlation on each of the adopted phases and for changes in normal active modes of the isolated groups D2h through the evolution of the active modes ν3 and ν2.